A Comparative Study of Lung Involvement Among Vaccinated and Unvaccinated Covid - 19 Patients - S Bhuvaneshwari; A T Sathiya Vinoth; M S Umamageswari; A Vijayamathy; S Jeevithan; Sabari Arasu; N I Blesson Sha Fogarty; Akshay Kumar; Ashok Kumar (Journal of Pharmaceutical Research, 2023)
COVID-19 caused by a novel agent SARS-CoV-2 progressed to a pandemic condition and resulted in a major public health concern worldwide, leading to social and economic issues at the same time. Vaccinated people getting infected with SARS-COV2 brings a dilemma among the population whether to get vaccinated or not. The primary objective of this study is to evaluate the impact of vaccination by comparing the lung involvement in vaccinated and un vaccinated Covid – 19 patients. Retrospective anonymised data of COVID-19 inpatients who underwent HRCT scan during the second wave of pandemic were collected through a validated data collection form, from the medical records of tertiary care private medical college hospital. Vaccinated and non-vaccinated COVID-19 positive participants of 33 each were included in the study. CT severity score (CTS), D-dimer, IL-6 level, oxygen requirement and duration of hospital stay were statistically analysed using appropriate methods. The mean age of the study participants were 56.93 ± 16.01 years. There was no statistical significance between both the groups with respect to gender distribution in vaccinated and unvaccinated groups. There was a statistically significant difference in mean CTS score(p<0.001) and oxygen requirement(p<0.05) among vaccinated and unvaccinated patients. There was no statistical significance between CORADS, IL-6, D – Dimer and duration of hospital stay. In COVID-19 patients, vaccination reduces the extent of lung involvement and the need for oxygen. The COVID-19 vaccination conundrum is somehow resolved by this study, which also gives us a clear picture of the vaccine's efficacy. Keywords COVID19, Vaccination, HRCT Scan, CORADS Severity